PEMANFAATAN ECO-ENZYME UNTUK PENINGKATAN KUALITAS LINGKUNGAN DAN KESUBURAN LAHAN DI DESA LEBO JAYA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - La Ode Santiaji Bande; La Ode Alwi; Teri Pakki; Saefuddin Saefuddin; La Ode Rustam (Universitas Halu Oleo, 2022)
The use of ecoenzymes is an effort to answer the problem of using inorganic fertilizers and environmental damage which is increasingly being used among farmers because their use has a negative impact. The target of implementing community service activities that are integrated with the Thematic KKN program are farmers in Lebo Jaya Village, Konda District, South Konawe Regency which have been designated as Organic Agriculture Areas. Most of the farmers in Lebo Jaya Village still use inorganic fertilizers and synthetic pesticides. The purpose of this activity is to provide farmers with an understanding of organic farming through training on making ecoenzymes. The output of this activity is that farmers are expected to gradually reduce or even no longer use inorganic fertilizers and start switching to the application of organic farming based on household waste.